B-cell targeted therapies in autoimmune encephalitis: mechanisms, clinical applications, and therapeutic potential - Shang, Haodong; Shen, Xinru; Yu, Xiaoxiao; Zhang, Jing; Jia, Yongliang; Gao, Feng (Frontiers in Immunology, 2024)
Autoimmune encephalitis (AE) broadly refers to inflammation of the brain parenchyma mediated by autoimmune mechanisms. In most patients with AE, autoantibodies against neuronal cell surface antigens are produced by B-cells and induce neuronal dysfunction through various mechanisms, ultimately leading to disease progression. In recent years, B-cell targeted therapies, including monoclonal antibody (mAb) therapy and chimeric antigen receptor T-cell (CAR-T) therapy, have been widely used in autoimmune diseases. These therapies decrease autoantibody levels in patients and have shown favorable results. This review summarizes the mechanisms underlying these two Bcell targeted therapies and discusses their clinical applications and therapeutic potential in AE. Our research provides clinicians with more treatment options for AE patients whose conventional treatments are not effective.